Pricing anomalies in a general equilibrium model with biased learning - Andrea Antico; Giulio Bottazzi; Daniele Giachini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
We investigate the emergence of momentum and reversal anomalies in a general equilibrium model with complete markets and cognitively biased agents, accounting for the presence of representativeness heuristic, conservatism, and anchoring and adjusting in their beliefs. We characterize anomalies by studying return autocorrelation patterns, price gaps following sequences of different events, and relative performances of suitably defined portfolios. These three characterizations are not equivalent. They capture different aspects of mispricing and relate differently to the behavioral heuristics that we consider. Overall, the model is generically able to reproduce the empirical evidence of momentum profits that subsequently revert.
Keywords: G41; D53; G12; G14; 330; Momentum; Reversal; Biased Learning; Bayesian Learning; Model Misspecification